CLINICAL AND PHYSIOLOGICAL ANALYSIS OF PREOXYGENATION METHOD - L. U. Kamenskaya; I. S. Kurapeev; V. I. Buravtsov (Вестник анестезиологии и реаниматологии)
The goal of this review based on the analysis and systematization of the results of numerous studies is to present the current view on preoxygenation method from the position of negative consequences development and opportunities for their prevention. Preoxygenation side effects and existing approaches to their prevention were analyzed. The role of high concentration of inhaled oxygen is highlighted as a potentially dangerous factor due to the development of post-surgical respiratory complications resulting from formation of resorption atelectasis. It has been proved that preoxygenation improvement is still the crucial issue for anesthesiology, and the search for ways of further safety enhancement for this technique has been discussed.